Quo Vadis LIPSS?—Recent and Future Trends on Laser-Induced Periodic Surface Structures - Jörn Bonse (Nanomaterials, 2020)
Nanotechnology and lasers are among the most successful and active fields of research and technology that have boomed during the past two decades. Many improvements are based on the controlled manufacturing of nanostructures that enable tailored material functionalization for a wide range of industrial applications, electronics, medicine, etc., and have already found entry into our daily life. One appealing approach for manufacturing such nanostructures in a flexible, robust, rapid, and contactless one-step process is based on the generation of laser-induced periodic surface structures (LIPSS). This Perspectives article analyzes the footprint of the research area of LIPSS on the basis of a detailed literature search, provides a brief overview on its current trends, describes the European funding strategies within the Horizon 2020 programme, and outlines promising future directions.